Assessment of Morbidity Pattern among the Rural and Urban Geriatric Population: A Cross Sectional Study - Jain, Manish; Prakash, Rahul; Jain, Rohit (National Journal of Community Medicine, 2017)
Introduction: Aging has been define as progressive, generalized impairment of function leading to lose of adaptive response to stress and growing risk of age related disease. Objective: to assess the morbidity pattern among the rural and urban elderly population and to identify possible factors influencing the morbidity pattern. Material and method: A cross- sectional study was carried out in rural and urban field practice areas of RNT Medical College, Udaipur, Rajasthan from January, 2015 to December, 2015. Study participants were subjected to- (a) Personal Interview and (b) Clinical Examination. Medical records if available with the respondents were scrutinized to confirm medical conditions. Results: Average numbers of illnesses per persons were recorded as 3.03 among rural and 3.08 among urban geriatric participants. Among rural elderly, Eye diseases were reported most commonly (63.6%) followed by diseases of cardio-vascular system (48.8%).Among urban geriatric participants, Diseases of cardio-vascular system were reported most commonly (59.2%) followed by eye diseases (57.6%). Psychosocial problems were more common among urban elderly. Conclusion: Overall morbidities were high among the study population, with non-communicable and degenerative diseases comprising the major burden of diseases.